2009
DOI: 10.18388/abp.2009_2469
|View full text |Cite
|
Sign up to set email alerts
|

Diminished expression of ICOS, GITR and CTLA-4 at the mRNA level in T regulatory cells of children with newly diagnosed type 1 diabetes.

Abstract: Diabetes mellitus is one of the most common chronic diseases in children. T regulatory cells (Tregs) modulate response to autoantigens and probably play a role in pathogenesis of type 1 diabetes (T1DM). The aim of the present study was the assessment of T regulatory cells including their percentages and expression of critical genes in these cells in children with newly diagnosed type 1 diabetes. The examined group consisted of 50 children with T1DM. A flow cytometric analysis of T-cell subpopulations was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…This is in keeping with recent data showing an association of ICOS expression and IL-10-producing capacity in human Tregs and Tr1 cells (15, 26, 39). Data showing reduced ICOS + Treg frequencies in the blood and tissues of patients with autoimmune diseases such as type I diabetes further support this contention (40). …”
Section: Discussionmentioning
confidence: 82%
“…This is in keeping with recent data showing an association of ICOS expression and IL-10-producing capacity in human Tregs and Tr1 cells (15, 26, 39). Data showing reduced ICOS + Treg frequencies in the blood and tissues of patients with autoimmune diseases such as type I diabetes further support this contention (40). …”
Section: Discussionmentioning
confidence: 82%
“…In the first study, the percentages of CD4 + CD25 high CD127 dim/− cells did not differ between children with T1D and controls, but mRNA levels of CTLA-4, ICOS1, IL-23, IL-27, SMAD3, and GITR were lower in Treg cells from children with T1D [80]. In the second study of 40 T1D patients, several Treg markers, including FoxP3, were evaluated [81].…”
Section: Gitr May Be More Useful Than Cd25 As a Marker Of Human Tregsmentioning
confidence: 99%
“…Minimal research has been conducted within the pediatric population. Current studies have noted a low frequency of Tregs in children with newly diagnosed T1D (Sanda et al 2008;Łuczyński et al 2009). Moreover, Sanda et al (2008) found no adverse effects of hyperglycemia and severe metabolic stress on the expression of FoxP3 and CD127.…”
Section: Discussionmentioning
confidence: 98%
“…Tregs have been implicated as a central control target in T1D progression and any defects in their development or function may represent a major predisposing factor for spontaneous autoimmunity in animals (Tritt et al 2008; Chen and Liu 2009). Some human studies have shown significantly reduced numbers of Tregs in T1D patients (Kukreja et al 2002;Łuczyński et al 2009). In contrast, other studies have not observed any differences in the frequency of these cells between diabetic patients and control subjects (Brusko et al 2005;Putnam et al 2005).…”
Section: Discussionmentioning
confidence: 99%